2012
DOI: 10.1016/j.indmarman.2012.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Configuring quality management and marketing implementation and the performance implications for industrial marketers

Abstract: Acknowledgements: We thank three anonymous reviewers for their useful comments on earlier

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 77 publications
(80 reference statements)
2
13
1
2
Order By: Relevance
“…García Bernal et al, 2004;Ryan and Moss, 2005). In contrast to previous findings (Ryan and Moss, 2005;Lai et al, 2012), the vast majority of organizations that are yet to achieve the high level of excellence do not exhibit varying patterns of adoption that would suggest that they would be adapting the model according to their preferences or limited resources. In fact, different approaches to the EFQM that would be in line with the patterns that have been observed in the QM literature, as for example those identified by Zhao et al (2004), are yet to be supported by assessments of Spanish organizations.…”
Section: Integrated Use Of Best Practicescontrasting
confidence: 99%
See 2 more Smart Citations
“…García Bernal et al, 2004;Ryan and Moss, 2005). In contrast to previous findings (Ryan and Moss, 2005;Lai et al, 2012), the vast majority of organizations that are yet to achieve the high level of excellence do not exhibit varying patterns of adoption that would suggest that they would be adapting the model according to their preferences or limited resources. In fact, different approaches to the EFQM that would be in line with the patterns that have been observed in the QM literature, as for example those identified by Zhao et al (2004), are yet to be supported by assessments of Spanish organizations.…”
Section: Integrated Use Of Best Practicescontrasting
confidence: 99%
“…Moreover, Yeung et al (2003) described high performers as organizations that take together elements of different nature (technical and social), thus adopting a systemic approach. In a similar vein, Lai et al (2012) concluded that when QM practices are implemented in an integrated way and at a high level, better performance is achieved. Consequently, based on this stream of literature, leading organizations in the EFQM model would be expected to embrace all enablers criteria at a high level of implementation.…”
Section: Can Approaches To Efqm Enablers Discriminate Organizations?mentioning
confidence: 95%
See 1 more Smart Citation
“…On this point Grover et al (2004) stated that, although customer satisfaction may be considered the key purpose of the TQM philosophy, customers are the primary focus of marketing. Some researchers began studying this subject in the 1990s (Morgan and Piercy, 1992;O'Neal and LaFief, 1992;Fram, 1995;Lai and Weerakoon, 1998;Mohr-Jackson, 1998a, b;Morgan and Piercy, 1998;Morris et al, 1999), but since 2000 only a few papers have addressed the impact of TQM on marketing performance (Longbottom et al, 2000;Sittimalakorn and Hart, 2004;Yam et al, 2005;Idris and Zairi, 2006;Santos-Vijande and Álvarez-González, 2009;Fuentes-Fuentes et al, 2011;Lai et al, 2012;Sarfarazi and Behboodi, 2012). Recently, Sarfarazi and Behboodi (2012) found a direct link between TQM and customer satisfaction.…”
Section: Third Cluster: Impact On Performance Of Csfsmentioning
confidence: 99%
“…Some works defend that Marketing and Quality are interrelated, highlighting the impact of Marketing on performance (e.g., Lai, 2003;Lai & Cheng, 2005;Lai, Yeung, & Cheng, 2012). Du and Wan (2008) defend that an emphasis on Quality needs the mediation of Marketing in order to have a significant impact on performance, whereas Homburg, Krohmer and Workman (2004) conclude that this mediation is partial.…”
Section: Introductionmentioning
confidence: 99%